Designing Teacher’s Participatory Decision-Making Model Using Delphi Combined Method and Interpretive Structural Modeling (ISM) (Case study: Second Year of Secondary Education in Lorestan Province) - Mokhtari, Seyyed Ali Mohammad; Pourhosseini, Ebrahim; Ghobadian, Moslem (Iranian Journal of Educational Sociology, 2022)
Purpose: The purpose of this study is to design a participatory decision-making model for teachers of the second year of secondary education in Lorestan province. In this regard, first, using library and field studies, the components of teachers' participatory decision-making were initially identified. Then, using interviews with experts and based on the Delphi method, the identified factors are finalized. Statistical society is given by the teachers of the second year of secondary education in Lorestan province. Methodology: The research was finalized using Delphi method including 5 main indicators of individual-personality traits, team-collective characteristics, communication-social characteristics, organizational characteristics and technical-specialized characteristics and related sub-indices. Then, using identified factors and based on interpretive structural modeling (ISM), a native model of teachers' participatory decision making was presented. Findings: Relationships between factors indicate the effectiveness of improving and eliminating challenges and promoting the participatory decision-making model of teachers. Conclusion: The factor of organizational characteristics is the most effective factor if factors such as individual-personality characteristics and communication-social characteristics have both effectiveness and effectiveness, as well as team-collective characteristics and technical-professional characteristics among the mentioned factors, only It is effective in determining the levels of effectiveness of the proposed indigenous model, practical suggestions were provided to address the challenges.